THE SYMBOLIC CONVERGENCE OF CROWDFUNDING IN POLITICAL CAMPAIGNS (CASE STUDY: NETIZEN DISCUSSIONS ON RIDWAN KAMIL`S FACEBOOK FANPAGE - Emeilia, Rindana Intan; Muksin, Nani Nurani (Universitas Muhammadiyah Yogyakarta, 2020)
Internet plays an important role as a medium of political communication, including its power for funding political campaigns known as crowdfunding. The success of crowdfunding in several countries, then adopted by Jabar Juara volunteers to raise funds political campaigns for Ridwan Kamil and Uu Ruzhanul Ulum in 2018 Governor Election. Socialization was carried out by uploading a video on title